Liver failure complicating segmental hepatic ischaemia induced by a PTFE-coated TIPS stent. Issue 4 (18th March 2009) - Vizzutti, F; Arena, U; Rega, L; Zipoli, M; Abraldes, J G; Romanelli, R G; Tarquini, R; Laffi, G; Pinzani, M
Abstract : The use of polytetrafluoroethylene (PTFE)-covered prostheses improves trans-jugular intrahepatic porto-systemic shunt (TIPS) patency and decreases the incidence of clinical relapses and re-interventions. Therefore, the improvement provided by covered stents might expand the currently accepted recommendations for TIPS use. Stent-related occlusion of the hepatic vein with consequent ischaemia of the corresponding liver parenchyma emerges as a novel complication reported in at least 5% of patients implanted with coated stents. However, this complication was reported to be mild, without signs or symptoms of liver failure, and self-limiting. We report a case of segmental liver ischaemia following PTFE-covered stent placement resulting in a marked impairment in liver function in a patient with hepatitis C virus cirrhosis implanted because of refractory oesophageal bleeding, thus expanding the severity range of this new procedural complication. Moreover, we discuss the possible involvement of additional pathogenetic mechanisms other than out-flow obstruction in the onset of coated-stent induced congestive liver ischaemia.